«Social-psychological picture» of patients with breast cancer and the problem of their psychological rehabilitation - I. V. Sukhoterin; N. V. Pavlova (Опухоли женской репродуктивной системы)
The results of social inquiry of 400 patients with breast cancer being on treatment in Belgorod Oncological Dispensary are shown. It is noted that 50–60 % of this women can not inquire themselves with psychological burden, they are in need of help of psychologists on all stages of treatment and observation. In connection with particular medical and social meaning of this problem the elaboration of effective programs of the psychological rehabilitation and social adaptation will be necessary.